(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
This article offers an overview of the significance of the Cat-stane inscribed stone in Kirkliston. The author cites various historical accounts of the inscription on this stone and why it might have been placed in Kirkliston. By comparing these older readings of the inscription to his own contemporary reading, the author attempts to decipher the meaning of what is written on the Cat-stane. He dismisses the proposals suggested in some of the older accounts of the stone that it may have been raised as a memorial for either King Constantine IV or a Pictish King named Geth. Instead he argues that this stone memorialises an Anglo-Saxon named Vetta son of Victa, who may have fought with the Picts against the Romans and could have been the grandfather of the Saxon leaders Hengist and Horsa. Meeting notes for 11 March, 1861 are appended.